Exercise training for intermittent claudication: critical analysis - Rumenapf, G.; Rother, Ulrich; Behrendt, C.; Uhl, C.; Gortz, H.; Morbach, S.; Sigl, M. (Gefässchirurgie, 2020)
Background The guidelines for the treatment of intermittent claudication (IC) recommend lifestyle improvement, risk factor management, pharmacotherapy for improvement of blood flow, as well as structured supervised exercise training (SET). Revascularization is not advised as the first line treatment. In Germany, the guideline recommendations and treatment reality of IC are substantially different. Methods The systematic literature search for the S3 guidelines on peripheral arterial occlusive disease (PAOD) of the German Society of Angiology (DGA) from 2014 was updated to 2020. Results If the pattern of arterial occlusions is suitable, a consistent implementation of SET can significantly enhance the walking distance. In general, however, the efficacy, availability and practicability of SET are limited and patient adherence is low. In contrast, revascularization for IC can improve or normalize the walking capacity faster than SET, with continuously increasing sustainability. The best results are obtained by the combination of revascularization and SET. Conclusion Revascularization plays an important role in the treatment of patients with IC, particularly as conservative treatment strategies using SET are not recognizably implemented in the German healthcare system. Better availability of SET could decrease the number of revascularizations, enhance the long-term success and reduce the cardiovascular risk.
CRIS-Team WoS Importer:2021-01-08